Risk factors for injuries in New Zealand older adults with complex needs: a national population retrospective study - Rebecca Abey-Nesbit (BMC, 2021)
Abstract Background Falls and falls-related injuries are common among older adults. Injuries in older adults lead to poor outcomes and lower quality of life. The objective of our study was to identify factors associated with fall-related injuries among home care clients in New Zealand. Methods The study cohort consisted of 75,484 community-dwelling people aged 65 years or older who underwent an interRAI home care assessment between June 2012 and June 2018 in New Zealand. The injuries included for analysis were fracture of the distal radius, hip fracture, pelvic fracture, proximal humerus fracture, subarachnoid haemorrhage, traumatic subdural haematoma, and vertebral fracture. Unadjusted and adjusted competing risk regression models were used to identify factors associated with fall-related injuries. Results A total of 7414 (9.8%) people sustained a falls-related injury over the 6-year period, and most injuries sustained were hip fractures (4735 63.9%). The rate of injurious falls was 47 per 1000 person-years. The factors associated with injury were female sex, older age, living alone, Parkinson’s disease, stroke/CVA, falls, unsteady gait, tobacco use, and being underweight. Cancer, dyspnoea, high BMI, and a decrease in the amount of food or fluid usually consumed, were associated with a reduced risk of sustaining an injury. After censoring hip fractures the risks associated with other types of injury were sex, age, previous falls, dyspnoea, tobacco use, and BMI. Conclusions While it is important to reduce the risk of falls, it is especially important to reduce the risk of falls-related injuries. Knowledge of risk factors associated with these types of injuries can help to develop focused intervention programmes and development of a predictive model to identify those who would benefit from intervention programmes.